New synthetic approach to a [1.1.6] metapara cyclophane derivative via Suzuki-Miyaura cross-coupling and ring-closing metathesis - Kotha, S; Mandal, K; Arora, KK; Pedireddi, R (Advanced Synthesis & Catalysis, 2005)
The synthesis of a [1.1.6] metapara cyclophane derivative, 1,5(1,4),3(1,3)-tribenzenacycloun-decaphan-8-ene-6,11-dione, has been achieved via the Suzuki-Miyaura cross-coupling of alpha,alpha'-dibromo-m-xylene with an arylboronic acid derivative followed by an allylation and ring-closing metathesis reaction sequence.
Keywords: Cyclophanes; olefin metathesis; Palladium; ruthenium; Suzuki-Miyaura cross-coupling